2021
DOI: 10.2147/phmt.s306411
|View full text |Cite
|
Sign up to set email alerts
|

Skin-to-Skin Care Practice and Its Associated Factors Among Postpartum Mothers in Gurage Zone, Southern Ethiopia: A Cross-Sectional Study

Abstract: Background Skin-to-skin care is placing an unclothed or diaper-only newborn baby on the mother’s bare chest, covered with a warm blanket. The World Health Organization recommends immediate, uninterrupted, and continuous mother–newborn skin-to-skin care practice almost immediately after birth. Despite this recommendation, separation of the newborn from the mother is common in many public health institutions. There was a limited study that examined the prevalence of skin-to-skin care practice and as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 21 publications
3
18
2
Order By: Relevance
“…Hence, they become highly non-compliant to health promotive newborn practices. Consistent with previous studies,13 26 our findings suggest that women who lived in rural residence reported lower odds of practicing skin-to-skin contact with their newborns. This association may largely be influenced by the preponderance of health facilities and services in urban areas 26.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Hence, they become highly non-compliant to health promotive newborn practices. Consistent with previous studies,13 26 our findings suggest that women who lived in rural residence reported lower odds of practicing skin-to-skin contact with their newborns. This association may largely be influenced by the preponderance of health facilities and services in urban areas 26.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with previous studies,13 26 our findings suggest that women who lived in rural residence reported lower odds of practicing skin-to-skin contact with their newborns. This association may largely be influenced by the preponderance of health facilities and services in urban areas 26. This study also revealed that the likelihood of practicing skin-to-skin contact was lower among women who delivered by caesarean section.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Placing an unclothed or diaper only newborn baby on the mother's bare chest or abdomen soon after birth and keeping them together continuously for at least 1 h regardless of the mode of delivery, place of delivery, and feeding methods ( 16 , 26 ). In this study, skin-to-skin care practice was measured dichotomously as “Yes” coded as 1 and “No” coded as 0 ( 14 ).…”
Section: Methodsmentioning
confidence: 99%
“…Even though skin-to-skin contact between neonates and their mothers has numerous benefits for improving the baby's survival, it is being poorly practiced, particularly in resource-limited settings ( 14 ). According to studies, Ethiopia has a low SSC practice that ranges from 28.1 to 35.3% in different parts of the country ( 15 , 16 ). Several studies reported that factors such as maternal education, number of ANC visits, the residence of the family, newborn birth weight, time of breastfeeding initiation after delivery, optimum breastfeeding content-wise, maternal knowledge status toward skin-to-skin contacts, maternal and infant benefits, preterm, Apgar score, route of delivery, the health status of the newborn, place of delivery, and late initiation of ANC follow-up affect the level of skin-to-skin practices ( 14 18 ).…”
Section: Introductionmentioning
confidence: 99%